Proteomic analysis of honey. Identification of unique peptide markers for authentication of NZ mānuka (Leptospermum scoparium) honey. (15th July 2021) - Bong, Jessie; Middleditch, Martin; Loomes, Kerry M.; Stephens, Jonathan M.
Highlights: Identification of unique peptides in NZ mānuka honey & L. scoparium nectar. 2. L. scoparium nectar peptides were not present in other plant species nectar. 3. Bottom-up proteomic approach using nano-liquid chromatography separation with HRMS. 4. Proteins were identified based on a predicted mānuka proteome and database searches. 5. Abstract: Proteomics is an emerging tool in food authentication that has not been optimised for honey analysis. In this study, we present a qualitative proteomic analysis of New Zealand mānuka ( Leptospermum scoparium ) honey. A total of fifty bee-derived proteins were identified in the honey, the most predominant being major royal jelly proteins (MRJPs). We also demonstrate for the first time the presence of unique nectar-derived proteins in mānuka honey. A total of 17 mānuka plant proteins were identified, a-third of which were putative pathogenesis-related proteins. Two proteins involved in drought tolerance were also identified. Twelve candidate peptides were selected as potential authentication markers based on their uniqueness to mānuka honey. Nectar analyses confirmed the origin and specificity of these peptides to L. scoparium nectar, thus presenting peptide profiling as a viable and novel approach for mānuka honey authentication. Raw data are available via ProteomeXchange with identifier PXD021730.